We have to prove that `log_a b = 1/(log_b a)`

Use the property for changing the base of logarithms: `log_a b = (log_c b)/(log_c a)`

Change the base of `log_a b` to b

`log_a b = (log_b b)/(log_b a)`

Use the property: `log_b b = 1`

=> `1/(log_b a)`

**This proves that **`log_a b = 1/(log_b a)`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now